Perlindungan Lahan Pertanian Dan Hak Asasi Petani Sebagai Instrumen Mewujudkan Ketahanan Pangan Berkelanjutan Di Indonesia - Saptaning Ruju Paminto; Brisha Putri Sovani; Adrysh Rojabulakbar; Muhammad Deva Setiawan; Muhammad Ricky Sholeh; Usama Al Qaida (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Protecting Sustainable Food Agricultural Land as an effort to prevent conversion of wetlands and protect farmers' rights is difficult. However, the real effort is to establish strict regulations. In some contexts, there are still several weaknesses in the policies taken by the government in protecting land. Moreover, in its implementation, potential conflicts of interest between regional governments who base their reasons on regional autonomy and the central government who want to protect food agricultural land could occur.